ENHANCING STUDENTS' SPEAKING PROFICIENCY: INVESTIGATING THE EFFICACY OF THE STORY COMPLETION TECHNIQUE - Liskinasih, Ayu; Marcelina, Pinky Anggi ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2023)
This study investigated the effectiveness of the Story Completion technique in improving students' speaking proficiency. It focused on secondary school students in Indonesia, addressing a research gap in this specific context. The study involved 60 participants divided into two groups, using a Quasi-experimental design. Data collection included pre-test and post-test speaking assessments. Analyzing the results with an Independent Sample t-test revealed that the Story Completion technique had a significant positive impact on students' speaking proficiency compared to traditional Storytelling. The statistical analysis confirmed the acceptance of the alternative hypothesis and rejection of the null hypothesis. Additionally, the N-Gain analysis indicated that the experimental group achieved a higher mean score, demonstrating superior speaking skills compared to the control group. In conclusion, this study establishes that Story Completion is an effective and engaging method for enhancing students' speaking proficiency. These findings provide support for the use of the Story Completion technique in teaching speaking skills.